Characterization of the complete mitochondrial genome of Syrphus vitripennis (Diptera: Syrphidae) - Daoxin Liu; Pengfei Song; Jingyan Yan; Jiuli Wang; Jiuxiang Xie (Mitochondrial DNA. Part B. Resources, 2020)
The complete mitochondrial genome of Syrphus vitripennis was sequenced and reported here. The circle genome of S. vitripennis is 16,185 bp in length. There are 38 sequence elements including 13 protein coding genes, 22 tRNA genes, 2 rRNA genes, and a control region. The order of all elements was the same with that of Eristalia cerealis. With two species from Muscidae and Drosophilidae as outgroups, phylogenetic relationships of eight Syrphidae species based on mitogenomes were in complete agreement with their taxonomic relationships based on morphological characteristics. Our result will provide more fundamental data to the development of the molecular systematics of Syrphidae.